Exploring The Influence of Mental Health and Academic Stress on The Academic Achievement of PLS-SEM Analysis Among First-Year College Students at Universitas Riau - Primahardani, Indra; Futra, Dedi; Rasmiwetti, Rasmiwetti; Albeta, Sri Wilda; Dahnuss, Dodi; Isjoni, M. Yogi Riyantama (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study was focused on analyzing the influence of mental health and academic stress on the academic achievement of first-year students. This research was conducted in the Study Program of Chemistry Education, Biology Education, Physics Education, Mathematics Education, History Education, Economics Education, Pancasila and Civics Education, at the Faculty of Teacher Training and Education (FKIP), University of Riau. The sample size for this study was 303 first-year students. The research data were collected using questionnaires distributed directly to students. The data were analysed using SmartPLS version 4.0. There was a significant effect of mental health on student academic achievement (p<0.05; calculated t-value = 8.592 > t-table value of 1.96), categorised as strong. Meanwhile, academic stress also had a significant effect on student achievement (calculated t-value = 2.106 > t-table = 1.96, p < 0.05), indicating a strong effect. Academic stress was also found to impact students' mental health (p<0.05). Simultaneously, the combination of mental health and academic stress was also found to influence academic achievement (p<0.05) significantly. A path analysis found that the path from academic stress to mental health to academic achievement was an effective predictor of first-year students' academic achievement. Path coefficient analysis identified this pathway as an effective model for improving student academic achievement. This research is expected to provide attention and policy guidance for first-year students' academic achievement at the Faculty of Teacher Training and Education, University of Riau.